Evaluation and Recommendation User Interface of Batamnews Based on User Experience using User-Centered Design - Angelino Sandy Kusuma; Indra Lukmana Sardi; Rosa Reska Riskiana (STMIK Budi Darma, 2022)
Batamnews is a media that presents news about Batam. Batamnews currently has an application that aims to make it easier for users to continue to be updated regarding news in Batam. But from the results of interviews and the distribution of questionnaires with Batamnews users, there are problems experienced by application users due to the User Interface which makes users uncomfortable using the application. Users feel that Batamnews is not optimal in terms of appearance, and the user's uninterested use of icons (symbols). In addition, Users complain about features that should be available but not in the app. Therefore, this study aims to make a design using the User-Centered Design (UCD) method because UCD focuses on user needs. Then for testing the design, the System Usability Scale (SUS) evaluation method will be used because it can be measured for effectiveness, efficiency, and satisfaction from users. The results of this study are recommendations for the User Interface Design of the Batamnews application and have an increased value on usability from 54 to 74 which is expected to be a reference for Batamnews application developers. So, it can be concluded that the UCD method can increase the SUS usability value in an application as well.